La vinculación asistencia humanitaria-desarrollo: puntos de encuentro y desencuentro en un mundo “unipolar” - Sáenz Ramírez, Paola (Revista Española de Desarrollo y Cooperación, 2023)
The entailment that must exist, or not, between the two major canalization process of the international cooperation: the humanitarian action and development aid, it continuous to be an open debate. For that reason, the present analysis will attempt to answer how and why the humanitarian action and development aid have been forced to ‘realign themselves’ in accordance with the changes in the international agenda, manly in the matter of human security; and which one are the opportunities and possibilities for the humanitarian action and development aid to cooperate between them.